Innovation and Employment Growth in Costa Rica; A firm-level analysis - Monge-González, Ricardo (2013)
This paper studies the degree to which innovation by Costa Rican manufacturing firms creates or displaces employment, how different innovation strategies affect employment, and how these effects vary by firm size and type of employment demand characteristics (skills and gender). In particular the research focuses on the differential effects of product and process innovations on employment growth. Particular attention was paid to identifying innovation impacts on employment generation by SMEs (small and medium-sized enterprises). In doing so, we estimate a model proposed in Harrison, Jaumandreu, Mairesse, and Peters (2008) using an IV approach with data from the Innovation Surveys for Costa Rica for the period 2006–2007. The results show that both product and process innovation are positively related to employment growth. Evidence was found for important differences in impacts by firm size and labor skills. The strategy of in-house innovation is very important as a driver of employment generation. Imported innovation does not seem to have an impact on employment growth.  The findings suggest that policies aimed at overcoming challenges faced by Costa Rican firms in becoming more innovative are also very important for generating new employment opportunities in the country.